Linking humans to food webs: a framework for the classification of global fisheries. Issue 7 (2nd August 2018) - Bieg, Carling; McCann, Kevin S; McMeans, Bailey C; Rooney, Neil; Holtgrieve, Gordon W; Lek, Sovan; Bun, Ngor Peng; KC, Krishna B; Fraser, Evan
Abstract : There is a widely acknowledged need to explicitly include humans in our conceptual and mathematical models of food webs. However, a simple and generalized method for incorporating humans into fisheries food webs has yet to be established. We developed a simple graphical framework for defining whole‐system inland fishery food webs that includes a continuum of fishery behaviors. This range of behaviors mimics those of generalist to specialist predators, which differentially influence ecosystem diversity, sustainability, and functioning. Fishery behaviors in this food‐web context are predicted to produce a range of "fishery types" – from targeted (ie specialist) to multispecies (ie generalist) inland fisheries – and relate to the socioeconomic status of fishery participants. Fishery participants in countries with low Human Development Index (HDI) values are highly connected through fisheries food webs relative to humans in more developed countries. Our framework shows that fisheries can occupy a variety of roles within a food‐web model and may thereby affect food‐web stability in different ways. This realization could help to improve sustainable fisheries management at a global scale.